Design and development of a handheld bluetooth-based application system framework for controlling and monitoring remote devices - Saadat, Md. Nazmus (2006)
For short range wireless communication, Bluetooth technology is well known standard while competing with other short range wireless standard like Infrared, WiFi, and UWB. Bluetooth is being used worldwide today. Its point to multipoint For short range wireless communication, Bluetooth technology is well known standard while competing with other short range wireless standard like Infrared, WiFi, and UWB. Bluetooth is being used worldwide today. Its point to multipoint and no line of sight facility has removed the obstacles that some other hugely used technology like IrDA had. This work focuses on designing and developing an application system framework for controlling and monitoring remote devices wirelessly using Bluetooth within its standard range. For example, any Bluetooth enabled PDA, laptop or mobile phone can be used for controlling the household devices like lights, air con or digital audio systems in room environment or this can be used for industrial machine controls and office environment for various purposes starting from switching devices to acquiring real-time data from working systems or from sensors. Also the system can be used for robotic aspects in short range distance and no line of sight facility has removed the obstacles that some other hugely used technology like IrDA had. This work focuses on designing and developing an application system framework for controlling and monitoring remote devices wirelessly using Bluetooth within its standard range. For example, any Bluetooth enabled PDA, laptop or mobile phone can be used for controlling the household devices like lights, air con or digital audio systems in room environment or this can be used for industrial machine controls and office environment for various purposes starting from switching devices to acquiring real-time data from working systems or from sensors. Also the system can be used for robotic aspects in short range distance. The system design went through number of different tests and real time simulations to assure performance issues. The results show that it provides the standard features of system services with acceptable quality in data transmission and reception and controlling remote devices and the user application and interfaces are very much convenient to interact with. Finally, a prototype has been developed according to the design. The test results measured using the prototype verify the system design and confirm the standard performance of services.